2017
DOI: 10.1111/hex.12634
|View full text |Cite
|
Sign up to set email alerts
|

Talking to the people that really matter about their participation in pandemic clinical research: A qualitative study in four European countries

Abstract: BackgroundPandemics of new and emerging infectious diseases are unpredictable, recurrent events that rapidly threaten global health and security. We aimed to identify public views regarding provision of information and consent to participate in primary and critical care clinical research during a future influenza‐like illness pandemic.MethodsDescriptive‐interpretive qualitative study, using focus groups (n = 10) and semi‐structured interviews (n = 16), with 80 members of the public (>18 years) in Belgium, Spai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 19 publications
(18 reference statements)
0
37
0
2
Order By: Relevance
“…Ethical issues also arose around equity in access to health care for participants and nonparticipants [44,50,59]. There were calls for international standards for the conduct of emergency research [21,51,60,62], [51], acceptable study designs [14] and simplified consent methods [2,3,6,25,37,46,51,70,74]. Some studies explored waivered consent [2,25,69,70,74] and/or proxy consent [69].…”
Section: Disseminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethical issues also arose around equity in access to health care for participants and nonparticipants [44,50,59]. There were calls for international standards for the conduct of emergency research [21,51,60,62], [51], acceptable study designs [14] and simplified consent methods [2,3,6,25,37,46,51,70,74]. Some studies explored waivered consent [2,25,69,70,74] and/or proxy consent [69].…”
Section: Disseminationmentioning
confidence: 99%
“…However, gaining proxy consent was also found to be challenging during emergencies [15]. A qualitative study set in Europe found public support for consent waiver for publicly funded, low-risk studies and routinely collected anonymised biological samples for research, and for advanced or verbal consent models for pandemics [70,74]. An interventional Ebola study set in Guinea reported patient preference for verbal consent [69].…”
Section: Disseminationmentioning
confidence: 99%
“…Patients agree with this approach, as shown by a number of studies conducted before the current pandemic. 7,8 Canada's clinical research infrastructure is being scaled quickly to meet these scientific and ethical imperatives, similar to trials that were conducted during the Ebola epidemic. 9 The Canadian Institutes of Health Research and its partners launched a rapid research funding opportunity on COVID-19 in February 2020, completing applications, submissions, peer review and initial funding decisions within 18 days.…”
Section: Generating Randomized Trial Evidence To Optimize Treatment Imentioning
confidence: 99%
“…Historically, low and middle income countries have borne the burden of infectious disease outbreaks, but more recently pandemics have exposed the lack of preparedness in well‐connected, economically‐stable, developed countries. Although patient‐centered research is critical during pandemics, each pandemic brings huge disruptions in essential clinical research . Coronavirus Disease (COVID‐19), with its asymptomatic transmission, symptoms mimicking those of influenza, and a human‐to‐human transmission rate of 4, has attained a pandemic state and exposed the vulnerability of our clinical research enterprise …”
mentioning
confidence: 99%